Water management in Penang: long-term solutions to crisis - Musa, Norwahida; Roslim, Salmah (Universiti Teknologi MARA, Kedah, 2025)
Water scarcity has become a pressing issue for many cities (Adnan, 2022), including Penang, Malaysia. With over 1.7 million people, Penang relies on limited water sources under stress from prolonged dry weather and rising consumption. Due to these conditions, the state prioritises short-term relief and longterm planning to secure water supplies. Air Hitam and Teluk Bahang dams currently have 27.6% and 25.2% capacity, respectively, causing Penang's water supply crisis. Tens of thousands of households and businesses across the state are threatened by this shortage. Since late 2023, Penang has experienced low rainfall, compounding the water crisis and increasing the risk of future shortages. A lack of rainfall has resulted in local water authorities being under increasing pressure to implement robust solutions to avoid a full-blown water shortage (Penang2030, 2024).